A supervised exercise intervention fails to improve subjective and objective sleep measures among older adults with and without HIV. Issue 5 (28th October 2020) - Hixon, Brian; Burgess, Helen J.; Wilson, Melissa P.; MaWhinney, Samantha; Jankowski, Catherine M.; Erlandson, Kristine M.
Abstract : Background: Chronic sleep disruption can have significant negative health effects and prior studies suggest that people with HIV (PWH) have disproportionately higher rates of sleep problems. Methods: We evaluated baseline sleep of sedentary, older adults (50–75 years) with ( n  = 28) and without HIV ( n  = 29) recruited into a 24-week exercise study. Subjective sleep quality was assessed with the Pittsburgh Sleep Quality Index (PSQI); objective sleep parameters were assessed using wrist-worn actigraphy. Regression models were used to investigate changes in outcomes. Results: Fifty-seven participants completed the intervention. At baseline, PWH had significantly lower sleep efficiency (88.7 [95% CI 86, 91]%) compared to controls (91.8 [95% CI 91, 93]%; p  = 0.02); other sleep measures indicated poorer sleep among PWH but did not reach statistical significance ( p  ≥ 0.12). Overall, sleep outcomes did not significantly change with the exercise intervention (all p  > 0.05). In adjusted analyses, PWH demonstrated a decrease in total sleep time (–22.1 [–43.7, –0.05] p  = 0.045) and sleep efficiency (–1.3 [–2.5, –.01], p  = 0.03) during the 24 weeks of exercise; these differences were attenuated and no longer significant after adjusting for exercise intensity. At the completion of the intervention, compared to controls, PWH had significantly poorer sleep by PSQI score (2.2 [0.6, 3.8]; p  = 0.006) and sleep efficiency (–2.8 [–5.4, –0.2]%; p  = 0.04). Conclusions: In this study, sleep disturbance was more prevalent in sedentary older PWH compared to uninfected controls. An exercise intervention had minimal effect on sleep impairments among PWH nor controls. Among older adults, interventions beyond cardiovascular and resistance exercise may be needed to significantly alter subjective and objective sleep outcomes.